2014
DOI: 10.1002/chem.201303366
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isolated Metal Atoms as Active Sites for Photocatalytic Hydrogen Evolution

Abstract: The process of using solar energy to split water to produce hydrogen assisted by an inorganic semiconductor is crucial for solving our energy crisis and environmental problems in the future. However, most semiconductor photocatalysts would not exhibit excellent photocatalytic activity without loading suitable co-catalysts. Generally, the noble metals have been widely applied as co-catalysts, but always agglomerate during the loading process or photocatalytic reaction. Therefore, the utilization efficiency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(92 citation statements)
references
References 25 publications
4
88
0
Order By: Relevance
“…Hollow sites, each missing three carbon atoms, on graphene were thought to be ideal anchoring sites for single Ni atoms after calculation 11b. Recently, theoretical screening with the aim of finding robust anchoring sites for SACs have been reported intensively, for example, for graphene,22e TiN,22c BN,32 θ ‐Al 2 O 3 ,22b TiO 2 ,9b and various metal nanoparticles 10. In fact, robust anchoring of the single atom to the support is not enough to achieve the potential of SACs.…”
Section: Concept Synthesis and Key Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hollow sites, each missing three carbon atoms, on graphene were thought to be ideal anchoring sites for single Ni atoms after calculation 11b. Recently, theoretical screening with the aim of finding robust anchoring sites for SACs have been reported intensively, for example, for graphene,22e TiN,22c BN,32 θ ‐Al 2 O 3 ,22b TiO 2 ,9b and various metal nanoparticles 10. In fact, robust anchoring of the single atom to the support is not enough to achieve the potential of SACs.…”
Section: Concept Synthesis and Key Issuesmentioning
confidence: 99%
“…The research and applications of SACs are rapidly being extended. In 2014, Yang and co‐workers for the first time reported the use of SACs of M 1 /TiO 2 in photocatalytic hydrogen evolution,9b where M is an isolated atom of Pt, Pd, Rh, or Ru strongly anchored to the support. As novel photocatalysts, M 1 /TiO 2 illustrated not only excellent stability for H 2 evolution, but also a 6–13 fold increase in photocatalytic activity compared with the metal clusters loaded onto TiO 2 .…”
Section: The Power Of Single‐atom Catalysis and Recent Advancesmentioning
confidence: 99%
“…[2][3][4] Experimentally,s ignificant progress has been made on the synthesis and characterization of single-metala toms on variouss ubstrates, such as metal, [5] graphene, [6,7] zeolites and open metal-oxides upports. [8][9][10][11][12][13][14][15][16][17][18] Theoretically,t he catalytic activities toward CO oxidation of single-metal atom embedded on the graphene [19][20][21][22][23] or graphene oxide [24] or BN nanosheet [25][26][27] or metal oxides [12,16,[28][29][30] have been studied. Wang et al performed ab initio simulations to understand the reaction mechanism of CO oxidation over ceria-supported Au particles, andt hey found that in the presence of CO, an isolated AuÀCO speciese merges to catalyze CO oxidationw ith the adjacent interface oxygen and subsequently the isolatedAureintegrates back into the nanoparticle after the reactioni sc ompleted.…”
Section: Introductionmentioning
confidence: 99%
“…Further research on noble-metal-based cocatalysts is therefore essential in the development of an efficient photocatalytic system that can specifically suppress the undesirable H 2 oxidation reaction (HOR), while preserving efficient H 2 evolution rate under light irradiation.Recently, oxidized platinum (Pt d + ) cocatalysts, which have the capacity for suppressing HOR, have been found to be efficient for HER from solar water splitting. [13][14][15] However, their potential as active materials for photoreactions has only received sporadic attention. Recent advances in ligand-assisted loading methods have fostered a renewed interest in stabilizing the valence state of Pt species (that is, PtO); [13] the regulation of cluster sizes enables the control over their electronic and physical properties.…”
mentioning
confidence: 99%